Spoilt for choice: different immunosuppressive potential of anaplastic lymphoma kinase inhibitors for non small cell lung cancer - Heine, Annkristin; Held, Stefanie Andrea Erika; Daecke, Solveig Nora; Flores, Chrystel; Brossart, Peter (Frontiers in Immunology, 2023)
Introduction: Several anaplastic lymphoma kinase (ALK)-inhibitors (ALKi) have been approved for the treatment of ALK-translocated advanced or metastatic Non Small Cell Lung Cancer (NSCLC), amongst crizotinib and alectinib. This forces physicians to choose the most suitable compound for each individual patient on the basis of the tumor´s genetic profile, but also in regard to toxicities and potential co-treatments. Moreover, targeted therapies might be combined with or followed by immunotherapy, which underlines the importance to gain detailed knowledge about potential immunomodulatory effects of these inhibitors. We here aimed to 1.) determine whether ALKi display an immunosuppressive effect on human dendritic cells (DCs) as important mediators of antigen-specific immunity and to 2.) dissect whether this immunosuppression differs among ALKi. Methods: We investigated the effect of alectinib and crizotinib on human monocyte-derived DCs (moDC) as most powerful antigen-presenting cells. We performed immunophenotyping by flow cytometry, migration, antigen uptake and cytokine assays. Results: Crizotinib-treated DCs showed reduced activation markers, such as CD83, decreased chemokine-guided migration, lower antigen uptake and produced inferior levels of pro-inflammatory cytokines, especially Interleukin-12. In contrast, the immunosuppressive potential of alectinib was significantly less pronounced. This indicates that crizotinib might profoundly dampen anti-tumor immunity, while alectinib had no unfavourable immunosuppressive effects. Conclusions: Our results implicate that current ALKi differ in their capacity to suppress the activation, migration and cytokine production of DCs as essential mediators of T cell immunity. We show that crizotinib, but not alectinib, had immunosuppressive effects on DCs phenotype and reduced DC function, thereby potentially impairing anti-tumor immunity.